Point defects in turbostratic stacked bilayer graphene - Gong, C; Lee, S; Hong, S; Yoon, E; Lee, G; Warner, J (Royal Society of Chemistry, 2017)
The special properties of graphene can be largely influenced by point defects in the lattice. However, TEM studies of topological defects in few-layered graphene have rarely been reported. In this work, the two simplest forms of point defects monovacancy and divacancy in twisted bilayer graphene are characterized using aberration-corrected transmission electron microscopy (AC-TEM) at 80 kV. A convenient approach by using a negative mask in the fast Fourier transform (FFT) has been applied to separate the image signal of the two graphene layers. In the study combined with density functional theory (DFT) calculations and tight-binding molecular dynamics simulations, the analysis of the defect structure and movement shows the stability and migration behavior of both defects. DFT calculations indicate that the migration of monovacancy in bilayer graphene needs to overcome a higher energy barrier.